The VariLift® Interbody Fusion System: expandable, standalone interbody fusion - Emstad E (Dove Medical Press, 2015)
Erik Emstad,1 Diana Cardenas del Monaco,1 Louis C Fielding,2 Jon E Block2 1Wenzel Spine, Inc., Austin, TX, 2The Jon Block Group, San Francisco, CA, USA Abstract: Intervertebral fusion cages have been in clinical use since the 1990s. Cages offer the benefits of bone graft containment, restored intervertebral and foraminal height, and a more repeatable, stable procedure compared to interbody fusion with graft material alone. Due to concerns regarding postoperative stability, loss of lordosis, and subsidence or migration of the implant, interbody cages are commonly used with supplemental fixation such as pedicle screw systems or anterior plates. While providing additional stability, supplemental fixation techniques increase operative time, exposure, cost, and morbidity. The VariLift® Interbody Fusion System (VariLift® system) has been developed as a standalone solution to provide the benefits of intervertebral fusion cages without the requirement of supplemental fixation. The VariLift® system, FDA-cleared for standalone use in both the cervical and lumbar spine, is implanted in a minimal profile and then expanded in situ to provide segmental stability, restored lordosis, and a large graft chamber. Preclinical testing and analyses have found that the VariLift® System is durable, and reduces stresses that may contribute to subsidence and migration of other standalone interbody cages. Fifteen years of clinical development with the VariLift® system have demonstrated positive clinical outcomes, continued patient maintenance of segmental stability and lordosis, and no evidence of implant migration. The purpose of this report is to describe the VariLift® system, including implant characteristics, principles of operation, indications for use, patient selection criteria, surgical technique, postoperative care, preclinical testing, and clinical experience. The VariLift® System represents an improved surgical option for a stable interbody fusion without requiring supplemental fixation. Keywords: TLIF, PLIF, ACDF, standalone cage